Factors affecting pesticides hazard to different kinds of pollinators (Bollettino di zoologia agraria e bachicoltura, 2024)
Ecological factors determining the possibility of intoxication by pesticides of 3 biological groups of pollinators (wild solitary bees, bumble bees and honey bees) were analizied. Toxicity and rate of hazard of 16 insecticides to bees under field conditions were determined. Different kinds of bees can be ranged by increase of susceptibility to insecticides as follows: bumble bee, honeybee and alfalfa leaf-cutting bee. The less hazardous for pollinators were pyrethroid insecticides, the most hazardous were organophosphorus ones.
Keywords: bees; ecological factors; insecticides; residues; toxicity